Kontribusi Beban Kerja Dan Insentif Terhadap kinerja Kurir J&T Express Pada Era Belanja Online Di Sumatera Barat - Koto, Dicky Febrian; Primanita, Rida Yanna (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
This study aims to see the contribution of workload and incentives to the performance of J&T express couriers in the era of online shopping in West Sumatra. The population in this study were J & T express couriers who worked in the cities of Payakumbuh, Bukittinggi, and lubuk crocodile with a total population and sample of 69 people. The sample method used was total sampling. Data were collected using a workload and incentive scale compiled by the researcher himself, the incentive scale uses measuring instruments that have been adapted by Saputra (2019) based on the dimensions compiled by Afandi (2018). The results of this study indicate that there is a positive and significant contribution between incentives to the performance of J & T couriers in West Sumatra. There is no significant contribution between workload and performance on J & T couriers in West Sumatra. Workload and incentives simultaneously contribute to the performance of J&T express couriers in West Sumatra.